Game changer—talent transfer pathways in sport: a systematic review - Green, Adeline; Fleischman, David; Mulcahy, Rory; Kean, Bridie (Frontiers in Sports and Active Living, 2024)
Research question Talent transfer, an accelerated sport pathway to expertise, holds considerable appeal for sports organisations. As an emerging area of academic research across a range of sport disciplines, there is opportunity for to advance knowledge and practice. This review aimed to (a) explore how talent transfer has been defined, to develop a synthesised definition; (b) systematically identify the factors that influence talent transfer; and (c) investigate how theory underpins and enhances understanding of talent transfer. Research methods A systematic review was conducted of 12 peer-reviewed journal articles on talent transfer using the PRISMA approach. Results and findings Aiming for a comprehensive, multidisciplinary perspective, the results: introduce a clear, synthesised conceptualisation of talent transfer as an accelerated sport pathway in which a highly trained athlete in one sport (donor sport), transitions to a new sport (recipient sport) with the potential of achieving high-performance success; systematically map influencing factors; and outline considered theories. Factors influencing talent transfer span individual, task-related, and environmental constraints. The review exposes a scarcity of theoretical foundation in current research, suggesting ecological dynamics as a promising approach to advance research and practice. Implications Practical and theoretical implications arise, emphasising the usefulness of a synthesised definition and a multifactorial approach for designing, implementing, evaluating, and researching talent transfer pathways. This benefits sports administrators, managers, and researchers.